Profile of evaluative thinking skills of chemistry education pre-service teachers on theme of carbohydrates in food chemistry lectures. Issue 1 (March 2021) - Sofia,; Permanasari, A; Sholihin, H; Supriyanti, FMT
Abstract: This study aims to determine the profile of evaluative thinking skills (ETs) of Chemical education pre-service teacher on the theme of carbohydrates in food chemistry (FC). The research method used was descriptive qualitative with a research sample of 31 students from 2013, 2014 and 2015 who have attended FC lectures in one of the Chemical Education department in South Sumatra. The instrument used was a test of ETs totaling 4 questions that had been validated. Indicators of ETs to be achieved include 1) Asking questions. 2) Seek deeper understanding through reflection and perspective, and 3) Making informed decisions in preparation for action. The results showed the profile of students' ETs on theme carbohydrates in FC lectures showed that the average student ETs were classified as low. Generally, students have demonstrated skills in asking questions adequately, but still show weaknesses in reflecting and perspective thinking. Likewise decision-making skills also need to be improved. ETs are needed so that students are able to do self-evaluation and introspect their own weaknesses to be able to think more forward.